2010
DOI: 10.1111/j.1365-2036.2010.04261.x
|View full text |Cite
|
Sign up to set email alerts
|

Indications of ‘atopic bowel’ in patients with self‐reported food hypersensitivity

Abstract: Patients with self-reported food hypersensitivity had a high prevalence of IBS and atopic disease. Atopic patients had increased intestinal permeability and density of IgE-bearing cells compared with non-atopic patients, but gastrointestinal symptoms did not differ between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 47 publications
2
37
0
7
Order By: Relevance
“…There have been several reports of increased prevalence of IBS among atopic patients, especially patients with asthma. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] In a large primary care study of general practitioner diagnosed IBS, the odds ratio for IBS among asthma patients was 2-fold that of controls. 47 Tobin et al 33 reported increased mucosal mast cells in a group of IBS patients with concurrent atopic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports of increased prevalence of IBS among atopic patients, especially patients with asthma. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] In a large primary care study of general practitioner diagnosed IBS, the odds ratio for IBS among asthma patients was 2-fold that of controls. 47 Tobin et al 33 reported increased mucosal mast cells in a group of IBS patients with concurrent atopic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Atopic patients were also shown to have increased intestinal permeability and density of IgE-bearing mast cells. 36 Sensitisation to food allergens, which were reported by patients to induce their gastrointestinal symptoms, was not shown (both via measurement of serum-specific food IgE and skin prick test).…”
Section: Discussionmentioning
confidence: 99%
“…As is known, dysregulated immune activation on the epithelial barrier surfaces is common in both allergy and IBS [17]. Lillestol et al [16] reported earlier that elevated numbers of IgEpositive cells in duodenal mucosa were found in patients with atopy compared to nonatopic patients. Besides, numbers of IgE-positive cells in duodenal mucosa were significantly correlated with levels of serum total IgE.…”
Section: Discussionmentioning
confidence: 99%
“…Lower GI symptoms such as diarrhea are common in children with allergy [14,15]. Intestinal permeability was significantly increased in patients with atopy compared to nonatopic patients [16]. Seasonal inhalation of birch pollen has been suggested to cause a duodenal increase in IgE-bearing cells [5].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that food hypersensitivity is more prevalent in patients with IBS and those with atopic diseases. 5 Patients with celiac disease or IBS experience clinically indistinguishable GI symptoms. 6 Despite these shortcomings, the significant association reported in this large-scale study lends further support to a common pathophysiological basis of these conditions.…”
mentioning
confidence: 99%